Strategi Periklanan pada Bisnis Retail - Veny Ari Sejati (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2015)
This research aims to analyze the benefits of advertising strategy of Poundland. The method used is a qualitative approach because its ability to produce an in-depth description to obtain an authentic understanding of the experience of the people concerned. The study found that Poundland conducted intensive advertising by utilizing important moments such as Halloween, Christmas, Mother Day, etc using Internet media, social media, and e-mail sent 1-2 times per week. Poundland also employs other media such as word of mouth spread among students. Catalog is also used as the print media to reach the consumers. Poundland uses communication technology and take advantage of important moments for advertising strategy. This description can be a reference for retail businesses in Indonesia to pay attention to important events in Indonesia such as national moments and utilizing non-traditional communication technologies as an advertising strategy.